Lateral mode behaviour in diode lasers based on coupled ridges. (December 2020) - Epanchinova, A A; Payusov, A S; Kornyshov, G O; Serin, A A; Kulagina, M M; Zhukov, A E; Gordeev, N Yu; Maximov, M V
Abstract: We present a study of diode lasers with two identical optically coupled ridges. Two coupled ridges were made gradually divergent to a distance of 50 μm which allowed creating three electrically isolated sections within a single laser. We carried out numerical simulations of the electromagnetic modes in the coupled ridge waveguide and calculated far-field patterns for each mode. The results are in good agreement with the experimental data. We have found that current spreading provided unwanted optical gain in the active region in between ridges and dramatically changed the structure of the lasing modes. The obtained numerical and experimental results can be used to design twin-ridge diode lasers able to operate in mode-locking regimes.